Recovery and viability of seeds ingested by goats - Harrington, K.C.; Beskow, W.B.; Hodgson, J. (New Zealand Plant Protection, 2011)
Seeds of eight plant species were fed to four penned goats on three separate occasions The faeces were collected over subsequent days then seeds were recovered and tested for viability Less than 10 of the ingested seeds survived passage through the goats for five of the species though 323 of broadleaved dock (Rumex obtusifolius) seeds and 192 of gorse (Ulex europeaus) seeds were excreted undigested The percentage of viable seeds ingested that remained viable when excreted ranged from 257 for broadleaved dock to 05 for variegated thistle (Silybum marianum) A large proportion of recovered seeds was excreted within 24 h of ingestion and all seeds had passed through the goats within 72 h Grazing by goats of weed seedheads is generally seen as beneficial due to large decreases in the number of viable seeds added to the soil However as all species established from intact goat dung potential exists for dispersal of weeds to new areas especially by feral goats